2016
DOI: 10.1007/s11248-016-9986-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of a novel HO-1 depletion model in the rat

Abstract: Although the protective role of HO-1 induction in various forms of kidney disease is well established, mechanisms other than heme catabolism to biliverdin, bilirubin and carbon monoxide have recently been identified. Unraveling these mechanisms requires the generation of appropriate animal models. The present study describes the generation of a HO-1 deficient Hmox1 rat model and characterizes its renal and extrarenal phenotype. Hmox1 rats had growth retardation and splenomegaly compared to their Hmox1 litterma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…A rat model of HO-1 deficiency was recently described by Atsaves et al [30]. Sprague-Dawley rats were employed in the study to reveal the role of HO-1 in various forms of kidney disease.…”
Section: Animal Models Of Ho-1 Deficiencymentioning
confidence: 99%
“…A rat model of HO-1 deficiency was recently described by Atsaves et al [30]. Sprague-Dawley rats were employed in the study to reveal the role of HO-1 in various forms of kidney disease.…”
Section: Animal Models Of Ho-1 Deficiencymentioning
confidence: 99%
“…While glomerular lesions were anecdotal in the mouse model, Atsaves et al found an increase in mesangial matrix and focal and segmental glomerulosclerotic lesions in Hmox1 −/− rats. These morphological findings were associated with increased blood urea nitrogen, serum creatinine and albuminuria, but interestingly there was no increase in iron deposits in the glomeruli, tubules or interstitium [20].…”
Section: About Heme Oxygenase-1 In Kidney 21 Why Is Ho-1 Particularmentioning
confidence: 88%
“…Kidney biopsies revealed increased mesangial proliferation and focal thickening of the capillary loops by light microscopy, and endothelial detachment in the glomerular capillary by electron microscopy [17,18]. Renal injuries were also present in both animal models invalidated for HMOX1, with some differences apparent between the mouse [19] and rat models [20]. In Hmox1 −/− mice, lack of functional heme oxygenase was responsible for enhanced susceptibility to oxidative stress [19], decreased hemophagocytosis of senescent red blood cells by tissue macrophages, increased hemolysis and redistribution of iron from splenic and hepatic macrophages to hepatocytes and renal proximal tubule cells [21].…”
Section: About Heme Oxygenase-1 In Kidney 21 Why Is Ho-1 Particularmentioning
confidence: 97%
“…Certain molecules that regulate metabolic functions in many cell types, including in immune cells, have been analyzed using genetically modified rats. Transgenic rats for heme oxygenase-1 (HO-1) under the control of the ubiquitous H-2Kb promoter (Braudeau et al, 2003) and HO-1 KO rats (Atsaves et al, 2017) have facilitated dissection of different aspects of HO-1 effects, particularly in kidney, where the lesions observed in rats differ from those in mice.…”
Section: Intracellular Moleculesmentioning
confidence: 99%